Fasting blood glucose is predictive of hypertension in a general Japanese population. Issue 1 (January 2019) - Kuwabara, Masanari; Chintaluru, Yaswanth; Kanbay, Mehmet; Niwa, Koichiro; Hisatome, Ichiro; Andres-Hernando, Ana; Roncal-Jimenez, Carlos; Ohno, Minoru; Johnson, Richard J.; Lanaspa, Miguel A.
Abstract : Objective: This study was conducted to identify whether higher fasting blood glucose levels is predictive of hypertension by a large-scale longitudinal design. Methods: We conducted a retrospective 5-year cohort study using the data from 13 201 Japanese individuals who underwent annual medical examinations in 2004 and were reevaluated 5 years later. This study included individuals without diabetes or hypertension between ages 30 and 85 years in 2004. The cumulative incidences of hypertension over 5 years in each 10 mg/dl of fasting blood glucose levels were calculated. Moreover, we examined risk factors and calculated odds ratios (ORs) for developing hypertension after adjustments for age, sex, BMI, smoking and drinking habits, dyslipidemia, chronic kidney disease, serum uric acid, and fasting blood glucose levels by logistic regression analyses. Results: We analyzed 10 157 participants (age: 48.9 ± 10.7 years; 43.4% men) without diabetes or hypertension in 2004. After multiple adjustments, higher baseline blood glucose level is an independent risk for hypertension (OR: 1.176; 95% CI 1.086–1.275), as well as aging, women, higher BMI, drinking habits, and higher serum uric acid. After stratifying by sex, higher baseline blood glucose level is an independent risk for hypertension both in women (OR: 1.295; 95% CI 1.135–1.478) and men (OR: 1.108; 95% CI 1.001–1.227). When we conducted the same analysis using glycated hemoglobin instead of blood glucose, glycated hemoglobin was not a risk for hypertension. Conclusion: Higher fasting blood glucose is an independent risk for developing hypertension. Further studies are needed to determine if treatment for elevated blood glucose can prevent developing hypertension.